Guidance for the evaluation of tuberculosis diagnostics that meet the World Health Organization (WHO) target product profiles: An Introduction to WHO Process and Study Design Principles - Denkinger, Claudia M. (The journal of infectious diseases, 2019)
High-priority target product profiles (TPPs) of the World Health Organization (WHO) establish important needs for tuberculosis diagnostic development. Here, we